A inclusão da pessoa com deficiência na educação superior: um estudo sobre o acesso, permanência e aprendizagem - Mendes, Hernestina da Silva Fiaux (2015)
The implementations of educational inclusion policies have required education systems, adjustments in school spaces with purpose to meet adequately the demand for students with various special educational needs who go to regular classrooms said. Organisations representing people with disabilities are working to seek better conditions for stay in these areas, as well as the provision of quality education. Given this reality, the education institutions whether Basic Education or Higher Education, need to fit a complementary task of host. After all, include is more of welcoming differences, it is necessary to review postures, and this requires behavior change and break with the prejudiced attitudes. The goal of our research is to understand the academic life of students with disabilities in higher education, identifying their problems and needs in graduation route, carrying out a study on access, retention and learning, trying to understand the process of inclusion of students with disabilities Higher Education institutions in the city of Umuarama, in the Paraná Northwest. For the study, were enrolled students surveyed, graduates and dropouts from 2008 to 2014. We used the assumptions of qualitative research / quantitative, descriptive, analytical because we believe is appropriate in understanding the lives of the participants in their everyday university, buscando- identify, through the analysis of data obtained in the interviews, the guiding principles of this study. The bibliographic database is of authors who discuss the education of persons with disabilities and educational inclusion in higher education. We bring as study units of meaning the difficulties and challenges faced by people with disabilities in higher education especially with regard to the process of teaching and learning, situations of prejudice and aspects of accessibility as well as the importance of family involvement in academic life, as fundamental elements for staying or leaving these students in HEIs.